Meningkatkan Hasil Belajar Dengan Model Discovery Learning Materi Aku Bangga Dengan Diriku Sdn 11 Tumbang Titi - Maria Erni (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Class action research conducted from July to August 2023. Students in phase A class 1 cannot read and write yet. Through the discovery learning learning model, the authors answer the challenge in an effort to improve student learning outcomes in Phase A first grade at Public Alementary School 11 Tumbang Titi. Challenges faced by writers; First; limited facilities in the form of books and scriptures. Second; the lack of interest of students in religious lessons. Third; creating effective and innovative media that can foster students' interest in learning. After carrying out the learning process the discovery learning model can improve student learning outcomes. Especially the Teaching Materials I Am Proud of Myself, sub-theme of My Identity to the sub-theme God Loves Me. This is evident in the increase in student learning outcomes in cycle I to cycle II starting from the cognitive aspect which increases 60% very well and 40% good. So there is an increase of 24% from cycle I. The flow of students' critical reasoning development is 75% lacking, and 25% is sufficient. Critical thinking skills in cycle II experienced a development of 9.1%. The aspect of faith and piety in cycle II is 2% of cycle one. The affective aspect in cycle II experienced growth of 6.25% from cycle I. The psychomotor aspect was 7.5% in cycle II of cycle I